Children of Isaac or Ishmael? a critical examination of Abu Hurayrah’s narration on the conquest of Constantinople - Mohammed Salim , Al-Amari; Fauzi , Deraman; Bensaid, Benouda (IDOSI Publications, 2012)
In his Sahih, Imam Muslim narrated that Abu Hurayrah spoke about the conquest of Constantinople based on a prophetic tradition attributed to the Prophet Muhammad in which he said: “The Hour will not rise until seventy thousand people from among the descents of Isaac conquer Constantinople.” Some Hadith interpreters were confused on the use of “Sons of Isaac” arguing that the true phrase must be “The Sons of Ishmael” instead. This they argued is inferred from other Prophetic traditions who describe the army conquering Constantinople as being from the city of the Prophet, the Medina which implies that the conquering army is rather Arabs, the descent of Ishmael. In this paper we seek to discuss this confusion and clarify the points of dispute around the proper understanding of this tradition. Our inquiry shows the confusion is only superficial and there is no conflict between these different traditions. Such a result implies the unnecessary undermining of the position of Imam Muslim in his hadith collection. This research discusses the doubt some Hadith commentators of Sahih Muslim find and their conclusion that the memory of some Hadith narrators skipped a word. We shall highlight the context of the Hadith, examine the question of doubt and position, discuss the scholarly views on this question and see what preferable and most reasonable answer should solve the question under study